The sound of danger - Barnett, Mac (Barnett, Mac. Mac B., kid spy, 2020)
"This is a story of stolen violins. It's got mummies, museums, sandwiches, hostages, and a dangerous showdown with the Russian Red Army Choir. Open this book to find out more about my adventures. But beware--this mission is top secret and very dangerous!" -- cover.